DEVELOPMENT OF AN ADAPTIVE DIGITAL ECOSYSTEM MODEL TOWARDS A SUSTAINABLE SMART CITY IN BANYUWANGI REGENCY - Ismail Nurdin; Etin Indrayani; Eem Nurnawaty; Dedhy Guntoro; Ikra Novar Rizqi; M. Rahimi Hasan (Jurnal Ilmiah Wahana Bhakti Praja, 2026)
This research is conducted to create an adaptive and sustainable Smart City ecosystem model for Banyuwangi Regency in response to challenges of digitalization and sustainable development in the region. The study emphasizes three pillars: building digital infrastructure, improving stakeholder cooperation, and formulating regulations conducive to technological innovation. Employing an exploratory qualitative method, the research was conducted through 18 in-depth interviews, direct observation, document analysis, and FGDs with diverse stakeholders. The collected data were analyzed using a paradigmatic model to construct a "Smart Sustainable City Ecosystem" tailored to Banyuwangi's characteristics and challenges. This study yields a digital ecosystem model incorporating policies to advance digital infrastructure, community digital literacy, and the regulation of technological innovation, adaptable across contexts. This development model would enable the continuity of Smart City development in Banyuwangi through an all-encompassing, adaptive strategy for environmental change. This study is only focused on the Banyuwangi area, and the data are collected from several stakeholders. It is suggested that future research, using multiple longitudinal studies, assess the model's effectiveness. Keywords: smart city, digital ecosystem, digital infrastructure, digital literacy, adaptive regulation.